High serum level of retinol and alpha-Tocopherol affords protection against oral cancer in a multiethnic population - Athirajan, V.; Razak, I.A.; Thurairajah, N.; Ghani, W.M.N.; Ching, H.N.L.; Yi, H.Y.; Peng, K.N.L.; Rahman, Z.A.A.; Mustafa, W.M.W.; Abraham, M.T.; Kiong, T.K.; Mun, Y.K.; et al. (Asian Pacific Education Press Ltd., 2014)
Background: A comparative cross-sectional study involving oral cancer patients and healthy individuals was designed to investigate associations between retinol, alpha-tocopherol and beta-carotene with the risk of oral cancer. Materials and Methods: This study included a total of 240 matched cases and controls where subjects were selected from the Malaysian Oral Cancer Database and Tissue Bank System (MOCDTBS). Retinol, alpha-tocopherol and beta-carotene levels and intake were examined by high-performance liquid chromatography (HPLC) and food frequency questionnaire (FFQ) respectively. Results: It was found that results from the two methods applied did not correlate, so that further analysis was done using the HPLC method utilising blood serum. Serum levels of retinol and alpha-tocopherol among cases (0.177 +/- 0.081, 1.649 +/- 1.670 mu g/ml) were significantly lower than in controls (0.264 +/- 0.137, 3.225 +/- 2.054 mu g/ml) (p<0.005). Although serum level of beta-carotene among cases (0.106 +/- 0.159 mu g/ml) were lower compared to controls (0.134 +/- 0.131 mu g/ml), statistical significance was not observed. Logistic regression analysis showed that high serum level of retinol (OR=0.501, 95% CI=0.254-0.992, p<0.05) and alpha-tocopherol (OR= 0.184, 95% CI=0.091-0.370, p<0.05) was significantly related to lower risk of oral cancer, whereas no relationship was observed between beta-carotene and oral cancer risk. Conclusions: High serum levels of retinol and alpha-tocopherol confer protection against oral cancer risk.